Guatemala : Request for Stand-By Arrangement-Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Guatemala. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This paper discusses a request from the Guatemalan authorities for an 18-month Stand-By Arrangement (SBA) with total access of SDR 630.6 million (about USD 951 million). Guatemala has a strong track record of macroeconomic stability. The economy is open and hence vulnerable to external shocks. The authorities have taken a number of upfront measures to mitigate the impact of the external shock and preserve macroeconomic stability. The program will support the authorities' policies and provide insurance against significant downside risks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet